2023
DOI: 10.1002/jsfa.12757
|View full text |Cite
|
Sign up to set email alerts
|

The technology of high‐power ultrasound and its effect on the color and aroma of rosé wines

Abstract: BackgroundThe application of high‐power ultrasound (US) has been studied extensively to obtain value‐added red wines using short maceration times. It is a technique of wide interest for the extraction of aromatic compounds and compounds responsible for color, so it could also be an important tool to use in the elaboration process of rosé wines. Thus, this study focused on the effect of the application of US on the phenolic, aromatic, and sensorial profile of rosé wines. For this, three different types of rosé … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The increase in alcohols and short-chain esters has also been reported for the sonication of red wine (Merlot). 18 In a related study, Fernandez et al 19 reported an increase in the concentration of alcohols and a significant reduction of fatty acids in Rose wine. However, the increase in alcohol concentration was attributed to the extraction of alcohol from the grape skin.…”
Section: Effect Of Sonication On the Volatile Profile Of Cashew Apple...mentioning
confidence: 93%
See 1 more Smart Citation
“…The increase in alcohols and short-chain esters has also been reported for the sonication of red wine (Merlot). 18 In a related study, Fernandez et al 19 reported an increase in the concentration of alcohols and a significant reduction of fatty acids in Rose wine. However, the increase in alcohol concentration was attributed to the extraction of alcohol from the grape skin.…”
Section: Effect Of Sonication On the Volatile Profile Of Cashew Apple...mentioning
confidence: 93%
“…Similarly, the use of ultrasound on cranberry juice was found to induce the formation of new volatile compounds through sonochemical transformation, which had a positive impact on the aroma . The effects of ultrasound on the aroma of wines have also been explored in some research studies. The findings mainly were beneficial, with some chemical changes observed. However, further research into the relationship between ultrasound and flavor is needed to gain a more comprehensive understanding of how this technology can enhance food product quality.…”
Section: Introductionmentioning
confidence: 99%
“…The application of a pilot-scale power ultrasound system (30 kHz, 2500 W, 8 W/cm 2 ) to crushed grapes facilitated the extractability of compounds from grapes to the must-wine, increasing the total phenol (18% and 23%) and tannin concentrations (43% and 30%) in the wine from less-ripened grapes and in the wine from partially rotten grapes, respectively [73]. The application of HPUS to obtain value-added red wines, using short maceration times, led to producing wine of a higher color intensity and a higher total polyphenol and anthocyanin content from grapes macerated for 4 h [74]. In this case, the application of US treatment (30 kHz, 2500 W, 8 W/cm 2 ) led to enhancing the extraction of volatile compounds in the must, especially the free terpene and norisoprenoid content (from 3.37 to 4.92 µg/L).…”
Section: Beveragesmentioning
confidence: 99%
“…In this case, the application of US treatment (30 kHz, 2500 W, 8 W/cm 2 ) led to enhancing the extraction of volatile compounds in the must, especially the free terpene and norisoprenoid content (from 3.37 to 4.92 µg/L). However, US caused the degradation of some phenolic compounds and vitamins, changes in color, the loss of anthocyanin, and other adverse effects on the food characteristics [74].…”
Section: Beveragesmentioning
confidence: 99%
“…In this sense, the efficacy of high-power ultrasound in rupturing the cell wall of skin cells has been demonstrated [ 9 , 10 ], with its consequent release of compounds of interest that are analyzed in wine (phenolic compounds, polysaccharides and aromatic compounds) considering the structural and compositional differences of cell walls depending on the grape ripening stage [ 11 , 12 ], microbiological alterations [ 12 ] and varietal nature [ 10 ]. Thus, conclusive results have been obtained from the optimization of the process of making value-added red wines through the use of US and usual processing times [ 10 , 11 , 13 , 14 ], as well as quality red, white and rosé wines with the use of US and shorter processing times [ 9 , 15 , 16 , 17 ], especially in those cases where US is combined with traditional techniques such as the addition of pectolytic enzymes [ 11 , 18 ], thus allowing not only for the improvement of the organoleptic characteristics of those wines whose initial potential is insufficient, but also for the reduction of the processing time without detriment to quality, increasing the productive capacity of wineries.…”
Section: Introductionmentioning
confidence: 99%